Investment Analisys Planning Untuk Kelayakan Ekonomi Penambangan Batubara pada Blok A PT. Tebo Agung International. - Sitra Wahyu Listiawati; Murad Murad (Departemen Teknik Pertambangan FT UNP, 2019)
Abstract. PT. Tebo Agung International is a company that will plan coal mining in Semambu Village, Sumay Subdistrict, Tebo District, an investment analysis and economic feasibility of the mine are needed to see the prospect of coal reserves in that location. Reference to the preparation of the economic model used is based on investment costs, production costs, and revenues from coal sales. To consider this, an economic feasibility analysis is needed. The parameters used to determine the economic feasibility of the coal production plan of PT. Tebo Agung International is Net Present Value (NPV), Internal Rate of Return (IRR) , Payback Period (PBP). The total reserves in Block A PT. Tebo Agung International is 7,000,000 tons, with an overburden volume of 31,000,000 bcm . Based on the amount of available reserves for coal getting and stripping activities OB, the number of loading and unloading equipment and transportation planned up to 2024 is 1 unit of Excavator Komatsu PC 300 and 3 units of Dump Truck Komatsu 220 and for 2025 until 2033 for coal getting and stripping activities OB is needed tool transport of 4 units of Dump Truck Komatsu 220 .The results of the investment analysis of the feasibility of the mining plan of PT. Tebo Agung International gets total numbers the profit earned is 159,036,405 . The feasibility of mining investment plans is obtained by a positive NPV of 49,516,154, an IRR value of 35 % with a MARR 6.5% and a payback period obtained at 4.27 years. Keywords: Production Plan, Costs, NPV, IRR, Payback Period